THE THOM CONDITION - Le, Dung Trang (Trường Đại học Đà Lạt, 2023)
In this note we explain the notion of the Thom condition for the Whitney stratifications of a complex analytic map. We give a question P. Deligne and indicate a possible way to answer it.